PERAN KELUARGA DALAM MENINGKATKAN SKILL LITERASI AL-QUR'AN PADA SISWA KELAS V MADRASAH IBTIDAIYAH MIFTAHUL HUDA DUWET KRAJAN KECAMATAN TUMPANG KABUPATEN MALANG - Muhammad Fahmi Junaidi; Isna Nurul Inayati (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
This study was conducted to describe the role of the family in improving the ability to read and write the Qur'an of fifth grade students of Madrasah Ibtidaiyah Miftahul Huda Tumpang. The type of research used is qualitative research with a case study approach. In carrying out this research, the researcher carried out 4 stages: pre-research, research implementation, data management, and research report writing. In collecting data, researchers used research instruments consisting of interviews, observations, and documentation. The results showed that the 6 students with the highest grades got pretty good results regarding the ability to read and write the Qur'an. Meanwhile, the 6 students with the lowest grades got poor results. The family environment or parents have a central and important role to improve student achievement including the ability to read and write the Qur'an properly and correctly. If the family environment is calm and conducive to the habituation of positive daily activities, it will have an impact on the psychological condition of the child so that the child is more focused on learning activities, especially on improving the ability to read and write the Qur'an.